Solitary wave propagation in surface stabilized ferroelectric liquid crystal cells - VIJ, JAGDISH; SONG, JANG-KUN (My University, 2008)
Solitary wave propagation in surface stabilized ferroelectric liquid crystal cells controlled by surface anchoring of the alignment layers is investigated for different conditions of alignment on the two opposite surfaces. We show that the critical field Ec, where the speed of the solitary wave becomes zero, is finite for asymmetric alignment on two surfaces. We also show that the polar anchoring energy difference (Deltawp) between the alignment layers can be calculated by measuring Ec, and this depends on the rubbing condition and the material of the alignment layer.
PUBLISHED
Keywords: Electronic & Electrical Engineering